Enhancing Students' Scientific Reasoning Skills in Renewable Energy Through Problem-Based Learning and Integrated Worksheets - Atika Fatharani; I Gusti Made Sanjaya; Yuni Sri Rahayu; Jung Won Lee (Program Studi Pendidikan IPA, Universitas Islam Lamongan, 2026)
This study evaluates the pedagogical effectiveness of integrating Problem-Based Learning (PBL) with structured student worksheets to enhance scientific reasoning skills. The primary objective is to address the global demand for sustainability education by focusing on renewable energy topics for junior high school students. The research employs a developmental model to design and evaluate a dual-learning approach through field trials and pre-experimental assessments. Findings indicate that the synergy of PBL and structured worksheets significantly improves students' capacity to analyze scientific data, construct evidence-based arguments, and verify complex assumptions. Students demonstrated a heightened ability to apply scientific knowledge to real-world energy challenges, making the learning process more relevant and engaging. The novelty of this research lies in its dual-approach framework, which systematically scaffolds reasoning processes while aligning with educational goals for sustainable development. This study concludes that while this integration provides a robust practical framework for science education, its success depends heavily on comprehensive teacher preparation in inquiry-based methodologies.